2015
DOI: 10.1016/j.enbuild.2015.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Building energy retrofits under capital constraints and greenhouse gas pricing scenarios

Abstract: This study demonstrates that capital availability needs to be considered while developing retrofit measures. Specifically, this study established a methodology using building energy simulations to determine optimal retrofit options over a range of NIST greenhouse gas pricing projections, full and half-price measure costs, and capital availability ranging from $1/ft 2-yr ($10.76/m 2-yr) to $100/ft 2-yr ($1076.39/m 2-yr), representing no capital constraint. The demonstration considers a sub-metered office buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, a simple payback period analysis (SPP) can be utilized from previous studies [33][34][35][36]. Wang et al [37] defined as the variables to be optimized based on the minimum simple payback period which Dahlhausen et al [38] analyzed the financial performance in their study. Weissbach et al [39] identified the simple payback period as energy payback time.…”
Section: Original Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a simple payback period analysis (SPP) can be utilized from previous studies [33][34][35][36]. Wang et al [37] defined as the variables to be optimized based on the minimum simple payback period which Dahlhausen et al [38] analyzed the financial performance in their study. Weissbach et al [39] identified the simple payback period as energy payback time.…”
Section: Original Research Papermentioning
confidence: 99%
“…Weissbach et al [39] identified the simple payback period as energy payback time. The simple payback period is as follows [33][34][35][36][37][38][39]:…”
Section: Original Research Papermentioning
confidence: 99%
“…There are many different ways to reduce greenhouse gas emissions from buildings. High-performance buildings have been regarded as one of the most advanced and effective ways of reducing greenhouse gas emissions [6][7][8]. The successful implementation of high-performance building requires the application of renewable energy systems (RES), as well as passive building design approaches [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The specific consumers of the electric energy are important to determine because the building energy modeling goal is to ultimately predict performance or choose energy conservation measures. Appropriate attribution is needed to be able to choose between component replacement and adjusted control scheme measures, especially when defining appropriate energy efficiency measures [20][21][22][23]. Therefore, this study aims to provide a novel method to accurately represent occupancy rates in building energy models, resulting in a reliable model calibration.…”
Section: Introductionmentioning
confidence: 99%